2014
DOI: 10.1149/2.0041409jes
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Quantify Reactive Chromium Vaporization from Solid Oxide Fuel Cell Interconnects

Abstract: High-temperature (>600 • C) reactive vaporization of Cr from chromia and stainless steels in oxidizing environments is an industrially relevant phenomenon that has been and will continue to be studied extensively for decades. Recently, many experimental techniques have been developed to measure Cr vaporization from stainless steel interconnect (IC) components within solid oxide fuel cell (SOFC) systems. Many of these techniques are based on an experimental method known as the transpiration method, which is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In their study a highly dense coating was ten times more effective while we found the difference to be only a factor of three. It should be mentioned that the measurements of Kurokawa were performed with a higher content of H 2 O in the gas (10 %), which is known to increase the rate of Cr vaporization [53,54]. Nevertheless, since the Cr evaporation rates reported for the bare alloy (9.8×10 -10 kg m -2 s -1 ) and with a highly dense spinel coating (2.3×10 -11 kg m -2 s -1 ) are comparable to those measured in the current work, it is interesting to compare the results for the more porous coatings as well.…”
Section: Cr Evaporationmentioning
confidence: 99%
“…In their study a highly dense coating was ten times more effective while we found the difference to be only a factor of three. It should be mentioned that the measurements of Kurokawa were performed with a higher content of H 2 O in the gas (10 %), which is known to increase the rate of Cr vaporization [53,54]. Nevertheless, since the Cr evaporation rates reported for the bare alloy (9.8×10 -10 kg m -2 s -1 ) and with a highly dense spinel coating (2.3×10 -11 kg m -2 s -1 ) are comparable to those measured in the current work, it is interesting to compare the results for the more porous coatings as well.…”
Section: Cr Evaporationmentioning
confidence: 99%
“…Vaporization of Cr from steel interconnects at the cathode‐side is an additional important issue, since volatile Cr species can easily migrate from the steel interconnect to the cathode electrode and form deleterious Cr‐rich compounds at electrode/electrolyte boundaries, with strong reduction of cathode electrochemical activity . According to recent studies, Cr vaporization is reduced at lower temperatures, although its relative importance compared to chromia oxide growth becomes greater under IT‐SOFC temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on the subject of fuel side coatings has focused on preventing austenitization, due to interdiffusion between the Ni or Ni/YSZ anode and the interconnect 15, 16. While literature suggests that the morphology of the protective oxide on the surface of the interconnect in fuel side environments is dual layered with an outer Cr‐Mn spinel and inner chromia layer as on the air side 16, it is established that the prevalence of a low oxygen partial pressure results in negligible rates of Cr evaporation 17, 18. Further, increased fuel utilization is expected to result in higher water vapor concentrations in the anode outlet gas, which in turn has been shown to increase the oxidation rate of the interconnect significantly and result in the formation of non‐protective Fe‐rich oxides 19.…”
Section: Introductionmentioning
confidence: 99%